Efeito da intervenção educativa grupal em cuidadoras idosas com Comprometimento Cognitivo Leve - Monteiro, Diana Quirino (Universidade Federal de São Carlos, 2018)
Introduction: The performance of cognitive functions is important for the maintenance of autonomy and independence of the elderly. The aging process, conceived as a worldwide phenomenon, encompasses a decline in cognitive functions. Associated with the diagnosis of Mild Cognitive Impairment (MCI), the fact of being a caregiver and the demands of care cause a series of complications that can be prevented, such as depressive symptoms, anxiety and cognitive deficit. Objective: to analyze the efficacy of a group health education program, composed of educational activities and combined with group dynamics, on depressive symptoms, anxiety, global cognition and their domains, and quality of life of elderly caregivers with MCI. Method: This is a quasi-experimental, controlled study in which 13 caregivers participated in the intervention Educação em Saúde (GES) and 11 in the Grupo Controle (GC) in the first half of 2016. They were evaluated before and after the intervention, interspersed between classes and dynamics totaling 20 meetings for 5 months by the following instruments: Addenbrooke's Cognitive Examination-Revised (ACE-R), Questionário de Mudança Cognitiva-22 (QMC-22), Inventário de Ansiedade e Depressão de Beck, WHOQOL-bref quality of life and Escala de Queixa de Memória (EQM). All ethical care was observed during the data collection and analysis process. The Mann-Whitney U tests for independent samples and Fisher's Exact Test to compare the groups (GES and GC) and the Wilcoxon and McNemar Test to evaluate the effects of the intervention were applied. Results: The effectiveness of the intervention on the cognitive domains "attention / orientation" (p = 0.03), "memory" (p = 0.002) and "visuospatial abilities" (p = 0.007) -R (p = 0.002), MEEM (p = 0.02) and on depression symptoms (p = 0.02). In the GC, no effects were observed, with the group remaining the same at the baseline and at the moment after intervention. Conclusion: The results suggest that the group Health Education program has a beneficial effect on symptoms of depression and cognitive abilities in elderly caregivers with MCI.
Effect of group educational intervention on elderly caregivers with Mild Cognitive Impairment
Keywords: Cuidadores; Disfunção cognitiva; Idoso; Cognição; Educação em Saúde; Caregivers; Cognitive dysfunction; Aged; Cognition; Health education; CIENCIAS DA SAUDE::ENFERMAGEM